Oxford urdu silsila "Hudhud" (for class 7) - Unsia bano (Oxford University Press; Pakistan, 2022)
Hudhud Class 7 is an engaging educational resource designed to enhance learning for seventh-grade students through comprehensive lessons, activities, and stories across various subjects.